2016
DOI: 10.1016/j.pocean.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic insights into the zooplankton dynamics of the eastern Weddell Sea

Abstract: The success of any efforts to determine the effects of climate change on marine ecosystems depends on understanding in the first instance the natural variations, which contemporarily occur on the interannual and shorter time scales. Here we present results on the environmental controls of zooplankton distribution patterns and behaviour in the eastern Weddell Sea, Southern Ocean. Zooplankton abundance and vertical migration are derived from the mean volume backscattering strength (MVBS) and the vertical velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 104 publications
(92 reference statements)
4
30
0
Order By: Relevance
“…For a more complete understanding of phytoplankton productivity and distribution, we suggest the following approaches: Extend the sampling to include fall and winter and to under‐ice environments with year‐round mooring or ice‐tethered buoy deployments, even in permanently ice‐covered areas. In order to disentangle the relative importance of bottom‐up and top‐down controls and to reveal possible climatic changes, time series measurements are needed (Cisewski & Strass, ). Sediment traps and other autonomous water samplers can collect ice algae and phytoplankton as sinking cells, marine snow and zooplankton fecal pellets (Turner, ). These platforms could potentially also be equipped with water sampling devices, camera systems, fluorescence, and nutrient sensors, as well as other probes which would provide a better understanding of mixed layer and upper water column processes across seasons.…”
Section: Biology I: Phytoplankton Of the Wgmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more complete understanding of phytoplankton productivity and distribution, we suggest the following approaches: Extend the sampling to include fall and winter and to under‐ice environments with year‐round mooring or ice‐tethered buoy deployments, even in permanently ice‐covered areas. In order to disentangle the relative importance of bottom‐up and top‐down controls and to reveal possible climatic changes, time series measurements are needed (Cisewski & Strass, ). Sediment traps and other autonomous water samplers can collect ice algae and phytoplankton as sinking cells, marine snow and zooplankton fecal pellets (Turner, ). These platforms could potentially also be equipped with water sampling devices, camera systems, fluorescence, and nutrient sensors, as well as other probes which would provide a better understanding of mixed layer and upper water column processes across seasons.…”
Section: Biology I: Phytoplankton Of the Wgmentioning
confidence: 99%
“…For example, the backscatter signal recorded by moored acoustic Doppler current profilers enables the estimation of zooplankton abundance. Using this technique, Cisewski and Strass () reported highest zooplankton abundance in the WG at the end of summer and lowest abundances during winter, following a seasonal pattern similar to that of phytoplankton. Furthermore, these authors found that DVM, characteristic of zooplankton, persisted throughout the austral night, with annual modulation centered at local noon in winter and summer solstices.…”
Section: Biology Ii: Food Web Of the Wgmentioning
confidence: 99%
“…Shallow dives observed in high sea ice concentration close to the Antarctic coast (10 ± 6% of the total dives for males) could correspond to specific foraging activity associated with the rich under-ice community of fish and invertebrates (Ainley et al, 1991). Moreover, these dives were mostly performed at night, where the diurnal vertical migration of adult krill (Euphausia crystallorophias), more pronounced in winter than summer (Siegel 2012;Flores et al, 2012b;Cisewski and Strass 2016) might attract various preys, such as Pleuragramma antarcticum (Fuiman et al, 2002).…”
Section: Male Foraging Behaviour In the Piz And Fizmentioning
confidence: 99%
“…(1) predator avoidance by staying away from the illuminated surface layer during the day and thus reducing the lightdependent mortality risk (Hays, 2003;Ringelberg, 2010;Torgersen, 2003) and (2) optimization of feeding, with the assumption that algal biomass is greater in the surface layer during evening hours and zooplankton rise to feed on it in the evening (Lampert, 1989). There are three general DVM patterns: (1) the most common one is nocturnal when zooplankton ascend around sunset and remain at upper depths during the night, descending around sunrise and remaining at depth during the day (Cisewski et al, 2010;Cohen and Forward, 2002). (2) Then there is a reverse pattern when zooplankton ascend at dawn and descend at dusk (Heywood, 1996;Pascual et al, 2017).…”
Section: Introductionmentioning
confidence: 99%